Variations Of Stocking Density And Type Of Feed For Growth And Survival Of Catfish (Clarias gariepinus) - Harianty, Harianty (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2018)
The research aimed to analyze the interaction, variation of stocking densities and effect of different types of feed on growth and survival of catfish (Clarias gariepinus) seeds in the plastic ponds and their interaction. The research was carried out in West Kotawaringin, Pangkalan Bun of Central Kalimantan from May to July 2017. A completely randomized design with two-factor experiment (stocking density and types of feed) were applied in the study, namely 100 seeds/m3 (treatment A1), 150 seeds/m3 (treatment A2), 100 % commercial pellet (treatment B1), 100 % chicken intestine (treatment B2), and 50 % commercial pellet and 50 % chicken intestine (treatment B3). Catfish with initial body weight 1 g were reared in the plastic pond (1x1x1x1 m3) for 60 days. The results showed that individual weight gain was range 35,22 to 60,12 g, the best treatment A2B3. Survival rate ranged from 40,00 – 76,66%, the best treatment A1B2.